Second-line Treatment of Non-Small Cell Lung Cancer: Focus on the Clinical Development of Dacomitinib - Zugazagoitia, Jon; Díaz, Asunción; Jimenez, Elisabeth; Nuñez, Juan Antonio; Iglesias, Lara; Ponce-Aix, Santiago; Paz-Ares, Luis (Frontiers in Medicine, 2017)
Dacomitinib is a second-generation, irreversible, covalent pan-HER tyrosine-kinase inhibitor (TKI). It showed potent EGFR signaling inhibition in experimental models, including first-generation TKI resistant NSCLC cell-lines. This preclinical efficacy did not translate into clinically meaningful treatment benefits for advanced, pretreated, molecularly unselected non-small-cell lung cancer (NSCLC) patients enrolled in 2 parallel phase III trials. Dacomitinib and erlotinib showed overlapping efficacy data in chemotherapy-pretreated EGFR wild-type (WT) patients in the ARCHER 1009 trial. Similarly, it failed to demonstrate any survival benefits as compared to placebo in EGFR WT subsets progressing on chemotherapy and at least 1 previous first-generation TKI (erlotinib or gefitinib) in the BR.26 trial. In the case of EGFR-mutant NSCLCs, a pooled analysis of the ARCHER 1009 and ARCHER 1028 trials comparing the efficacy of dacomitinib versus erlotinib in chemotherapy pretreated, EGFR TKI naïve patients showed a trend to a longer progression free survival and overall survival in favor of dacomitinib that did not reach statistical significance, with a higher rate of treatment related adverse events (mainly skin rash, paronychia and gastrointestinal toxicities). On the other hand, the clinical activity in patients with EGFR-mutant NSCLCs with acquired TKI resistance that were included in phase II/III trials was equally poor (response rate [RR] < 10 %; progression-free survival [PFS] 3-4 months). Therefore, with the results of the ARCHER 1050 trial (NCT01774721) still pending, the current clinical development of dacomitinib is largely focused on EGFR-mutant, TKI naïve patients. Here, we review the most relevant clinical data of dacomitinib in advanced NSCLC. We discuss the potential role of dacomitinib in pretreated EGFR WT and EGFR mutant (TKI naïve and TKI resistant) patients. Finally, we briefly comment the available clinical data of dacomitinib in HER2-mutant NSCLC patients.